Directed reprogramming of comprehensively characterized dental pulp stem cells extracted from natal tooth - Pisal, Rishikaysh; Suchanek, Jakub; Siller, Richard; Soukup, Tomas; Hrebikova, Hana; Bezrouk, Ales; Kunke, David; Micuda, Stanislav; Filip, Stanislav; Sullivan, Gareth; Mokry, Jaroslav (Scientific reports, 2018)
The aim of this study was to extensively characterise natal dental pulp stem cells (nDPSC) and assess their efficiency to generate human induced pluripotent stem cells (hiPSC). A number of distinguishing features prompted us to choose nDPSC over normal adult DPSC, in that they differed in cell surface marker expression and initial doubling time. In addition, nDPSC expressed 17 out of 52 pluripotency genes we analysed, and the level of expression was comparable to human embryonic stem cells (hESC). Ours is the first group to report comprehensive characterization of nDPSC followed by directed reprogramming to a pluripotent stem cell state. nDPSC yielded hiPSC colonies upon transduction with Sendai virus expressing the pluripotency transcription factors POU5F1, SOX2, c-MYC and KLF4. nDPSC had higher reprogramming efficiency compared to human fibroblasts. nDPSC derived hiPSCs closely resembled hESC in terms of their morphology, expression of pluripotency markers and gene expression profiles. Furthermore, nDPSC derived hiPSCs differentiated into the three germ layers when cultured as embryoid bodies (EB) and by directed differentiation. Based on our findings, nDPSC present a unique marker expression profile compared with adult DPSC and possess higher reprogramming efficiency as compared with dermal fibroblasts thus proving to be more amenable for reprogramming.
Keywords: buněčná diferenciace; karyotyp; Humans; embryoidní tělíska; Induced Pluripotent Stem Cells; lidé; Biomarkers; Cells, Cultured; Natal Teeth; Gene Expression Regulation, Developmental; indukované pluripotentní kmenové buňky; Stem Cells; biologické markery; Karyotype; Dental Pulp; kultivované buňky; Cell Differentiation; transkriptom; Transcriptome; Embryoid Bodies; fibroblasty; vývojová regulace genové exprese; předmléčné zuby; kmenové buňky; Cellular Reprogramming; zubní dřeň; Fibroblasts; přeprogramování buněk